Problematika Guru dalam Penggunaan Media Pembelajaran Sekolah Menengah Atas di Kota Medan - Sanas Tasia Sihaloho; Nadratul Aini Lubis; Cahya Putri Ramadhani; Alvian Maranalom Siregar; Nurmala Berutu; Syukrie Hidayat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Revolution 4.0 equips educators with the knowledge, abilities and skills to teach students effectively by using technological resources such as educational media such as Canva, Kahoot, Quiziz, and other platforms. Students by utilizing technological resources such as educational media such as Canva, Kahoot, Quiziz , and other platforms . The aim of this research study is to understand the theoretical problems or problems that teachers encounter when using learning media in Medan City High Schools. This is to understand the basic problems or problems that teachers encounter when using teaching media in Medan City High Schools. One of the research methods used in this research is the descriptive qualitative research method. This research is descriptive research with qualitative methods. The techniques used are documentation, observation and interviews. Research findings show that research shows that there are problems with the teaching methods used in high schools in Medan, including inconsistent use of teaching media and problems with the use of teaching media in these schools.There are problems with the teaching methods used in high schools in Medan. Medan, including inconsistent use of teaching media and problems with the use of teaching media in the school.